TAFI Meets the Sticky Ends - Booth, Nuala A. (Thrombosis and Haemostasis, 2001)
The coagulation and fibrinolytic system are often considered as separate entities, despite the obvious connection that one produces fibrin, the substrate for the other. A potent example of a more subtle and yet important connection lies in thrombin’s ability to generate an inhibitor of fibrinolysis. This exemplifies the pivotal role of thrombin in haemostasis, a consequence of its broad range of activities. Thrombin activates the zymogen form of a basic carboxypeptidase, generating an active enzyme called carboxypeptidase U, carboxypeptidase R, plasma carboxypeptidase B or TAFIa, thrombin activable fibrinolysis inhibitor (reviewed in 1-4; references from the reviews are not cited here). The activated carboxypeptidase removes C-terminal basic residues from fibrin. C-terminal Lys residues are key to binding t-PA and plasminogen, and thus to generating plasmin activity, a mechanism by which partially-lysed fibrin amplifies plasmin formation. The removal of these C-terminal Lys residues therefore decreases local fibrinolytic activity (Fig. 1). Several recent studies, two of which appear in this issue of Thrombosis and Haemostasis (5, 6), add to our knowledge of this activity and its potential role in thromboembolic disease.